Copolymerisation of Propylene Oxide and Carbon Dioxide by Dinuclear Cobalt Porphyrins. Issue 11 (18th September 2013) - Anderson, Carly E.; Vagin, Sergei I.; Hammann, Markus; Zimmermann, Leander; Rieger, Bernhard
Abstract Two dinuclear cobalt porphyrins comprising different structural tethering motifs at the porphyrin periphery were synthesised, along with a representative mononuclear cobalt porphyrin, and their catalytic activities tested towards carbon dioxide–propylene oxide copolymerisation in the presence of bis(triphenylphosphoranyl)ammonium chloride cocatalyst. The catalytic activities of the mononuclear and the bis‐para‐tethered dinuclear cobalt porphyrin with selective formation of poly(propylene carbonate) are largely comparable, showing no benefit of dinuclearity in contrast to the case of cobalt salen complexes and suggesting that polymer growth proceeds exclusively from one metal centre. The alternative bis‐ortho‐tethered porphyrin demonstrated considerably reduced activity, with dominant formation of cyclic propylene carbonate, as a result of hindered substrate approach at the metal centre. Time‐resolved UV/Vis spectroscopic studies suggested a general intolerance of the cobalt(III) porphyrin catalysts towards the copolymerisation conditions in the absence of carbon dioxide pressure, leading to catalytically inactive cobalt(II) species. In the presence of carbon dioxide, the bis‐ortho‐tethered catalyst showed the fastest deactivation, which is related to an unfavourable steric arrangement of the linker fragment, as was also confirmed by NMR spectroscopic measurements.